FPGA-Based Lightweight Hardware Architecture of the PHOTON Hash Function for IoT Edge Devices - Al-Shatari, M.O.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
The design of cryptographic engines for the Internet of Things (IoT) edge devices and other ultralightweight devices is a crucial challenge. The emergence of such resource-constrained devices raises significant challenges to current cryptographic algorithms. PHOTON is an ultra-lightweight cryptographic hash function targeting low-resource devices. The currently implemented hardware architectures of PHOTON hash function utilize a large amount of resources and have low operating frequencies with a low rate of throughputs. Maximum operating frequency and throughput of PHOTON architecture can be improved but at the cost of larger area utilization. Therefore, to improve the area-performance trade-offs of PHOTON hash function, an iterative architecture is implemented in this work. The concern is with the most lightweight version of PHOTON hash function with the hash size of 80 bits. It is implemented and verified on several Xilinx and Altera Field Programmable Gate Array (FPGA) devices using their synthesis and simulation tools. Low-cost and high-processing FPGA devices were both considered. The design is optimized for performance, whereas the area utilization is also taken into consideration. The overall performance and logic utilization are benchmarked with the existing implementations. The results show an improvement rate of 10.26 to 51.04 in the speed performance and a reduction rate of 7.55 to 60.64 in area utilization compared to existing implementations of PHOTON hash functions. Â© 2013 IEEE.